As implicações dos restos a pagar na gestão da saúde pública: o caso de Mato Grosso - Alencar, Alisson Carvalho de (2015)
The health issue is the center of national and international discussion about the need for development of public policies to be adopted by public agencies. Therefore, the State has an obligation to implement public policies that provide at all, concrete actions aimed at safeguarding the right to health. From this perspective, the objective of the research is to evaluate the implications of remains to pay in the management of public health of Mato Grosso, in the years 2008 to 2014. In that intent, from documentary research, literature and field it was observed that the state is inserted into a vicious cycle of remains to pay. Expenses dammed in the period maintained a dynamic evolution, damaging the financial implementation of the priority programs of Mato Grosso health. The programmatic financial realization is no longer considered optimal in 2008, with 92% of performance, to be characterized as a regular in 2014, with 66% of execution. Through the case study, it was identified that there isn't way to Mato Grosso get excellent results in the implementation of the interests of their society if the state meets the credibility shaken as against creditors, by excessively delaying its financial commitments without respect, or have the ability to perform the approved budget, by purchasing goods and contracting services through emergency mechanisms that increase the cost of buying public and enhance the power of the companies, in the implementation of the budget. In addition to damage the budget and financial programming, creating real parallel budgets, it is concluded that the excess costs passed on the year in which should occur for subsequent, damaged the quality of public services run on state health, hindering the realization of this right fundamental, essential to life.